Feminisme and Sexual Harassment: Gerakan #Meetoo Pada Mahasiswa Fakultas Ilmu Sosial Universitas Islam Negeri Sumatera Utara - Nasution, Kevin Rasyid Sabili; H, Haryati; Salsabilla, Clara Adinda; Marbun, Nurabni Rahmadani; Purba, Maulida Salsabila; Hutabarat, Rizky Octaviani Aulia (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The phenomenon of sexual violence in academic environments is a serious concern, including at the State Islamic University of North Sumatra (UINSU). This study examines how the #MeToo movement, which is rooted in feminism and an intersectional perspective, provides space for students of the Faculty of Social Sciences to speak out and fight against sexual violence. Data shows that many cases are not reported due to social stigma, patriarchal culture, and lack of trust in reporting mechanisms. The #MeToo movement was adopted by UINSU students through a digital platform to open up discussion space, support victims, and raise collective awareness about this issue. The study uses a phenomenological approach and qualitative methods to explore students' experiences, with in-depth interviews and observations as data collection techniques. The findings show that sexual violence is not only an individual problem, but also a reflection of gender inequality that is institutionalized in social and cultural structures. Challenges in the form of conservative resistance and stereotypes towards feminism are major obstacles in creating a safe academic environment. This study recommends strategic steps, including providing a safe complaint channel, gender equality education, and collaboration between students and institutions in building an inclusive campus culture. By integrating Islamic values, UINSU can become a model of educational institution that upholds justice, equality, and protection for victims of sexual violence. The #MeToo movement on campus has the potential to create sustainable systemic change in the academic environment.